Decentralisation for Development - Shrestha, Bihari Krishna (Water Nepal, 2003)
The devolution of decision-making authority to local levels has remained an illusive goal even now that Nepal is a multiparty democratic polity. However, Self-help groups (SHGs) can successfully perform many natural resource management functions. In fact, these groups have emerged as successful example of decentralized institutions that can fulfill local level governance tasks. This paper argues that SHGs are a potent institutional arrangement for bringing about accountability at the local level.Water Nepal Vol.9-10, No.1-2, 2003, pp.321-326